Propuesta de puntos de corte para indicación de la obesidad abdominal entre adolescentes - Fernandes, Rômulo Araújo [UNESP]; Chritofaro, Diego Giulliano Destro; Codogno, Jamile Sanches [UNESP]; Buonani, Camila [UNESP]; Bueno, Denise Rodrigues [UNESP]; De Oliveira, Arli Ramos; Da Costa Rosa, Clara Suemi [UNESP]; Freitas, Ismael Forte [UNESP] (My University, 2009)
Background: The absence of critical values for the cardiovascular risk identification among Brazilian adolescents represents an important limitation. Objectives: To prepare critical values for the waist circumference and to analyze its efficiency in indicating increased values of the arterial pressure. Methods: Transversal study that evaluated 1,145 adolescents, from 11 to 17 years old (536 of the male sex and 609 of the female), their body weight values, stature, resistance, reactance, tricipital cutaneous fold, waist circumference and arterial pressure (n = 334) were collected. The abdominal obesity was indicated by waist circumference values. Results: The obese adolescents presented higher waist circumference values and, independently of the gender and age group, there was a significant relation between the waist circumference values and all the adiposity indicators adopted in the study. The proposed critical values presented higher sensibility in indicating increased values of the arterial pressure. Conclusions: The critical values proposed for the waist circumference were more sensitive in the indication of increased values of the blood pressure. However, other studies to investigate their efficacy in the indication of other clinical and laboratorial parameters are still needed.
Proposal of cut points for the indication of abdominal obesity among adolescents
Keywords: Abdominal circunference; Adiposity; Adolescent; Hypertension; Overweight; Risk factors